Superfine tungsten-nickel-iron composite powder and preparation method thereof
By performing segmented carbon thermal reduction and deep hydrogen reduction treatment on WO3, NiO and Fe2O3 powders, combined with the nucleation and reduction effects of nanocarbon black particles, ultrafine tungsten-nickel-iron composite powder with uniform particle size distribution and high dispersion was successfully prepared. The problem of difficulty in preparing ultrafine tungsten-nickel-iron composite powder in the prior art was solved, and the fine crystallization of high-performance tungsten alloys was achieved.
Patent Information
- Application Number
- CN202411605284.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to prepare ultrafine tungsten-nickel-iron composite powder with uniform particle size distribution and high dispersion at low cost and high efficiency, resulting in insufficient fine crystallization of tungsten alloys and difficult to meet the demand for high-performance tungsten alloys in cutting-edge technical fields.
WO3, NiO and Fe2O3 powders are used for segmented carbon thermal reduction and deep hydrogen reduction treatment. Nanocarbon black particles are used as nucleation agents and reducing agents to regulate the nucleation and growth process of WO3 reduction to W, which significantly improves the shape of W. The core rate reduces the particle size of W.
It has achieved the ultrafine tungsten-nickel-iron composite powder with uniform particle size distribution and high dispersion, which solved the problem of difficulty in preparing ultrafine tungsten-nickel-iron composite powder in the prior art. It is suitable for sintering and preparing fine crystal/ultra-fine crystal tungsten-nickel-iron alloys, and improved The density and mechanical properties of the alloy are obtained.
Smart Images

Figure CN119457042A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ultrafine powder material preparation, and specifically relates to an ultrafine tungsten-nickel-iron composite powder and a preparation method thereof. Background Art
[0002] Tungsten-nickel-iron alloy is a dual-phase composite material with body-centered cubic W grains as the matrix and low-melting-point face-centered cubic metal Ni and Fe elements as the bonding phase. Due to its good mechanical properties, it has been widely used in aerospace, electronic information and military industries. In recent years, with the development of science and technology and the needs of society, the rapid development of tungsten alloy systems and preparation technologies has continued to be promoted. The melting point of tungsten is as high as 3410℃. The W grain size of the coarse-grained tungsten alloy prepared by the traditional high-temperature liquid phase sintering method can reach 40μm~50μm. Due to the problems of coarse grains and poor uniformity of organization, it is difficult to meet the demand for high-performance tungsten alloys in the field of cutting-edge technology. According to the Hall-Petch effect, grain refinement can significantly improve the mechanical properties of tungsten alloys. In order to prepare fine-grained tungsten alloys, domestic and foreign researchers have conducted a lot of research, such as changing the alloy composition, adding grain growth inhibitors, or adopting new alloy forming technologies, and have achieved certain results. However, due to the neglect of the front-end powder making process, the problem was not solved from the source, resulting in insufficient degree of grain refinement of the current tungsten alloy. The "bottom-up" powder metallurgy method is considered to be the most effective method for producing fine-grained tungsten alloys. It has obvious advantages in terms of versatility in controlling microstructure, the ability to develop alloys and composite materials with complex chemical properties, and near-net forming of samples with complex geometric shapes. Raw material powder is an important part of determining material properties and manufacturing costs. The performance of the powder largely affects the mechanical properties and quality of subsequent products. Therefore, to develop high-performance tungsten-nickel-iron alloy materials, it is necessary to first prepare fine-grained tungsten-nickel-iron powder raw materials. At present, the low-cost, high-efficiency and industrialized preparation of ultrafine tungsten-nickel-iron composite powders is still a difficult problem, and has become a "bottleneck" link in the commercial preparation and application of powder metallurgy fine-grained / ultra-fine-grained tungsten-nickel-iron alloys.
[0003] At present, mechanical alloying and spray drying-hydrogen reduction are the two most commonly used processes for preparing ultrafine tungsten-nickel-iron composite powders in the industry. Mechanical alloying refers to mixing element powders such as W, Ni and Fe in a high-energy planetary ball mill, and using the collision of ball milling media with the powder to achieve powder crystal refinement. Although this technology is suitable for large-scale industrial production, long-term ball milling will cause equipment wear and introduce impurities, affecting the purity of the powder. Spray drying is a thermochemical synthesis method that atomizes the solution by physical methods to obtain ultrafine composite powders. However, in the subsequent hydrogen reduction process, the precursor powder prepared by this technology, due to the existence of a chemical vapor transport (CVT) mechanism, the generated water will react with W to form a gas phase hydrate (WO2(OH)2). At the same time, due to the thick material layer, the gas phase hydrate concentration is high and the number of nuclei is small. The prepared tungsten powder has a large particle size, usually in the micron level, which makes it difficult to prepare ultrafine tungsten-nickel-iron composite powders.
[0004] In summary, the currently prepared ultrafine tungsten-nickel-iron composite powder still faces many problems. Therefore, how to achieve the preparation of ultrafine tungsten-nickel-iron composite powder and control the powder particle size at low cost and high efficiency is a big problem. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing ultrafine tungsten-nickel-iron composite powder in view of the deficiencies of the above-mentioned prior art. The method uses WO3, NiO and Fe2O3 powders as tungsten source, nickel source and iron source powders for segmented carbon thermal reduction and deep hydrogen reduction treatment in sequence, and uses nano carbon black particles as nucleating agent and reducing agent to effectively regulate the nucleation and growth process of WO3 reduction to W, significantly improve the nucleation rate of W, reduce the particle size of W, and obtain ultrafine tungsten-nickel-iron composite powder with uniform particle size distribution and high dispersion, which solves the problem that it is difficult to prepare ultrafine tungsten-nickel-iron composite powder in the prior art.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing ultrafine tungsten-nickel-iron composite powder, characterized in that the method comprises the following steps:
[0007] Step 1: dry-mix, crush and disperse WO3, NiO and Fe2O3 powders to obtain pre-treated tungsten source, nickel source and iron source powders;
[0008] Step 2: uniformly mixing the pretreated tungsten source, nickel source and iron source powders obtained in step 1 with the nano carbon black particles with the aid of an anhydrous ethanol solution, and obtaining a mixture after drying;
[0009] Step 3: After the mixture obtained in step 2 is laid, it is subjected to a segmented carbon thermal reduction treatment to obtain a pre-reduced powder;
[0010] Step 4: Lay the pre-reduced powder obtained in step 3 and perform deep hydrogen reduction treatment to obtain ultrafine tungsten-nickel-iron composite powder.
[0011] The invention uses WO3, NiO and Fe2O3 powders as raw materials, and uses nano carbon black particles as nucleating agents and reducing agents in a carbon thermal reduction process. First, the WO3, NiO and Fe2O3 powders are crushed, dispersed and mixed by dry mixing, and then the nano carbon black particles are mixed evenly with the WO3, NiO and Fe2O3 powders in an anhydrous ethanol solution. After drying, a composite powder mixture in which the nano carbon black particles are evenly distributed in the WO3, NiO and Fe2O3 powders is obtained, which effectively avoids the agglomeration of the nano carbon black particles, improves the mixing uniformity of the nano carbon black particles with the WO3, NiO and Fe2O3 powders, and is conducive to obtaining ultrafine tungsten-nickel-iron composite powders with uniform particle size and composition. Then, the mixture is subjected to a segmented carbon thermal reduction treatment, and the nano carbon black particles are used as reducing agents and nucleating agents. First, NiO and Fe2O3 in the mixture are reduced to γ-(Ni, Fe) solid solution at a lower reduction temperature, and then the nanocrystalline WO3 in the mixture is reduced to W powder and a small amount of WO2 at a higher reduction temperature. In this reduction process, the finer nucleating agent nanocarbon black particles significantly increase the number of nucleations, and the porosity between the nanocrystalline WO3 and the nanocarbon black particles is high, and has excellent dispersibility and uniformity, effectively preventing the agglomeration growth between the W powder particles, and effectively refining the particle size of the reduction products W and WO2; Finally, the pre-reduced powder is subjected to deep hydrogen reduction treatment to reduce WO2 to W. In this reduction process, due to the low content of WO2, the production of gas-phase hydrates containing W is also low, which inhibits the migration ability of W, thereby realizing the preparation of ultrafine W powder. The above-mentioned combined effects jointly improve the uniformity and dispersibility of the W particle size, thereby obtaining ultrafine tungsten-nickel-iron composite powder.
[0012] The above-mentioned method for preparing ultrafine tungsten-nickel-iron composite powder is characterized in that the mass of the WO3, NiO and Fe2O3 powders in step one is measured according to 93% W-4.9% Ni-2.1% Fe.
[0013] The above-mentioned method for preparing ultrafine tungsten-nickel-iron composite powder is characterized in that the average particle size of WO3 in step 1 is 40 μm to 50 μm, and the specific surface area is greater than 7 g / cm 3 , composed of nanocrystalline WO3 with an average grain size of less than 100nm, the average grain size of NiO is 0.5μm to 1μm, the average grain size of Fe2O3 is 0.5μm to 1μm, the rotation speed of the dry mixing crushing and dispersion is 200rpm to 300rpm, and the time is 2h to 6h. The preferred WO3 is easier to crush and disperse, which is conducive to subsequent uniform mixing with nano carbon black particles to obtain ultrafine tungsten-nickel-iron composite powder with finer average grain size and better dispersibility.
[0014] The above-mentioned method for preparing an ultrafine tungsten-nickel-iron composite powder is characterized in that the average particle size of the nano carbon black particles in step 2 is 20nm to 50nm, and the nano carbon black particles are amorphous structures, the mass content of carbon in the nano carbon black particles is greater than 99%, and the mass of the nano carbon black particles is 7.2% to 10.5% of the mass of the tungsten source powder; the uniform mixing method is wet mixing ball milling, the speed used is 200rpm to 250rpm, and the time is 2h to 4h. The preferred nano carbon black particles have fine particle size and large specific surface area, so they have excellent dispersibility. As a nucleating agent in the process of WO3 reduction to W, the number of W nuclei is significantly increased, and the particle size of W particles is reduced, thereby obtaining ultrafine tungsten-nickel-iron composite powder, so that the preparation process of the present invention is significantly superior to the traditional mechanical alloying method and spray drying-hydrogen reduction method.
[0015] The above-mentioned method for preparing an ultrafine tungsten-nickel-iron composite powder is characterized in that the thickness of the material layer after the mixture is laid in step 3 is less than 30 mm, the reduction temperature of the segmented carbon thermal reduction treatment is 650°C and 1050°C to 1100°C, the reduction time is 2h to 4h, and the mass purity of the argon atmosphere used in the segmented carbon thermal reduction treatment is greater than 99.99%. The preferred atmosphere conditions and segmented carbon thermal reduction process parameters enable WO3, NiO and Fe2O3 powders to be gradually reduced to W, WO2, Ni and Fe, and are also conducive to strengthening the migration of tungsten sources during the WO3 reduction process, improving the nucleation rate and controlling the growth process.
[0016] The above-mentioned method for preparing an ultrafine tungsten-nickel-iron composite powder is characterized in that the average particle size of the pre-reduced powder in step three is 100nm to 300nm.
[0017] The above-mentioned method for preparing an ultrafine tungsten-nickel-iron composite powder is characterized in that the thickness of the material layer after the pre-reduction powder is laid in step 4 is less than 30 mm, the reduction temperature of the deep hydrogen reduction treatment is 800°C to 900°C, the time is 2h to 4h, and the mass purity of the hydrogen atmosphere used in the deep hydrogen reduction treatment is greater than 99.99%. The preferred laying material layer thickness and the corresponding process parameters of the deep hydrogen reduction treatment not only ensure that the reaction gas and the product gas are easily diffused into the material layer, improving the reduction efficiency, but also ensure the gas phase migration rate of the tungsten source, thereby exerting the nucleation and particle size control effect of the nano carbon black particles, and obtaining a powder product with uniform particle size distribution and good dispersibility.
[0018] The above-mentioned method for preparing an ultrafine tungsten-nickel-iron composite powder is characterized in that the average particle size of the ultrafine tungsten-nickel-iron composite powder described in step 4 is less than 300nm.
[0019] In addition, the present invention also provides an ultrafine tungsten-nickel-iron composite powder, characterized in that it is prepared by the above method.
[0020] Compared with the prior art, the present invention has the following advantages:
[0021] 1. The present invention uses WO3, NiO and Fe2O3 powders as tungsten source, nickel source and iron source powders to perform segmented carbon thermal reduction and deep hydrogen reduction treatment in sequence, and uses nano carbon black particles as nucleating agent and reducing agent to effectively regulate the nucleation and growth process of WO3 reduction to W, significantly improve the nucleation rate of W, reduce the particle size of W, and obtain ultrafine tungsten-nickel-iron composite powder with uniform particle size distribution and high dispersion.
[0022] 2. The present invention adopts nano carbon black particles with low cost and excellent dispersibility as nucleating agent and reducing agent in the segmented carbon thermal reduction process respectively, and adopts dry grinding and dispersion and wet grinding and mixing to solve the problem that oxide raw materials and nano carbon black particles are difficult to mix evenly due to size differences and the agglomeration problem of nano carbon black particles, which is conducive to obtaining ultrafine tungsten-nickel-iron composite powder with uniform particle size distribution and good dispersibility, avoiding the disadvantages of large average particle size, poor dispersibility and high impurity content caused by the existing process, providing a new idea for the preparation of ultrafine tungsten-nickel-iron composite powder, and has high industrial application value.
[0023] 3. The present invention uses nano carbon black particles as a reducing agent and nucleating agent in the process of reducing WO3 to W, which significantly increases the number of nuclei, and the void ratio between the finer nucleating agent and the nano carbon black particle reducing agent is high, which effectively prevents the agglomeration growth between the W particles, thereby obtaining an ultrafine tungsten-nickel-iron composite powder.
[0024] 4. The present invention prepares ultrafine tungsten-nickel-iron composite powder with an average particle size of less than 300 nm, and the preparation industry is simple, the particle size control effect is good, the price is low, and it is suitable for large-scale engineering applications.
[0025] 5. The ultrafine tungsten-nickel-iron composite powder of the present invention is suitable for sintering to prepare fine-grained / ultrafine-grained tungsten-nickel-iron alloys, has a wide range of applications, effectively improves the density of tungsten-nickel-iron alloys, and is beneficial to improving the mechanical properties of alloy materials.
[0026] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the pretreated tungsten source, nickel source and iron source powders and nano carbon black particles prepared in Example 1 of the present invention.
[0028] Figure 2 This is a SEM image of the ultrafine tungsten-nickel-iron composite powder prepared in Example 1 of the present invention.
[0029] Figure 3 This is the XRD diagram of the ultrafine tungsten-nickel-iron composite powder prepared in Example 1 of the present invention.
[0030] Figure 4 This is a TEM image of the ultrafine tungsten-nickel-iron composite powder prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0031] Example 1
[0032] This embodiment includes the following steps:
[0033] Step 1: dry-mix WO3, NiO and Fe2O3 powders to obtain pre-treated tungsten source, nickel source and iron source powders; the mass of the WO3, NiO and Fe2O3 powders is measured according to 93% W-4.9% Ni-2.1% Fe; the average particle size of the WO3 is 40 μm, and the specific surface area is greater than 7 g / cm 3 , composed of nanocrystalline WO3 with an average grain size of less than 100nm, the average grain size of NiO is 0.5μm, and the average grain size of Fe2O3 is 0.5μm; the rotation speed of the dry mixing crushing and dispersion is 200rpm, and the time is 2h;
[0034] Step 2: uniformly mix the pretreated tungsten source, nickel source and iron source powders obtained in step 1 with the nano carbon black particles with the aid of anhydrous ethanol solution, and obtain a mixture after drying; the average particle size of the nano carbon black particles is 20nm, and the nano carbon black particles are amorphous structures, the mass content of carbon in the nano carbon black particles is greater than 99%, the mass of the nano carbon black particles is 7.2% of the mass of the tungsten source powder, i.e., WO3, and the mass of the anhydrous ethanol solution is 60% of the mass of WO3; the uniform mixing method is wet mixing ball milling, the speed used is 200rpm, and the time is 2h;
[0035] Step 3: The mixture obtained in step 2 is laid to a material layer thickness of 30 mm and then subjected to a two-stage carbon thermal reduction treatment. The mass purity of the argon atmosphere used is greater than 99.99%. The reduction temperatures of the two-stage carbon thermal reduction treatment are 650° C. and 1050° C., and the time is 2 h to obtain a pre-reduced powder with an average particle size of 100 nm.
[0036] Step 4: After the pre-reduced powder obtained in step 3 is spread to a material layer thickness of 20 mm, a deep hydrogen reduction treatment is performed, and the mass purity of the hydrogen atmosphere used is greater than 99.99%, to obtain an ultrafine tungsten-nickel-iron composite powder; the deep hydrogen reduction treatment is: heating to 800°C at a heating rate of 5°C / min and then keeping warm for 2 hours.
[0037] According to the test, the average particle size of the ultrafine tungsten-nickel-iron composite powder prepared in this embodiment is 200 nm.
[0038] Figure 1 The SEM images of the pre-treated tungsten source, nickel source and iron source powders and nano carbon black particles prepared in this example are shown in FIG. Figure 1 It can be seen that WO3 is a micron-sized particle formed by the agglomeration of many small nanocrystalline particles, which provides a good condition for the preparation of ultrafine tungsten-nickel-iron powder; the average particle size of NiO and Fe2O3 powder is about 500nm; and the microscopic morphology of nano carbon black particles is relatively loose, with good dispersion and an average particle size of 20nm.
[0039] Figure 2 This is the SEM image of the ultrafine tungsten-nickel-iron composite powder prepared in this example. Figure 2 It can be seen that the ultrafine tungsten-nickel-iron composite powder has good dispersibility and finer particle size.
[0040] Figure 3 The XRD pattern of the ultrafine tungsten-nickel-iron composite powder prepared in this example is as follows: Figure 3 It can be seen that the ultrafine tungsten-nickel-iron composite powder contains only two phases, W and γ-(Ni, Fe, W).
[0041] Figure 4 TEM image of the ultrafine tungsten-nickel-iron composite powder prepared in this embodiment. Figure 4 It can be seen that the ultrafine tungsten-nickel-iron composite powder has a finer particle size and excellent dispersibility. The ultrafine tungsten-nickel-iron composite powder is a composite powder formed by substitution and solid solution of W atoms in the Ni-Fe solid solution lattice.
[0042] Example 2
[0043] This embodiment includes the following steps:
[0044] Step 1: dry-mix WO3, NiO and Fe2O3 powders to obtain pre-treated tungsten source, nickel source and iron source powders; the mass of the WO3, NiO and Fe2O3 powders is measured according to 93% W-4.9% Ni-2.1% Fe; the average particle size of the WO3 is 45 μm, and the specific surface area is greater than 7 g / cm 3 , composed of nanocrystalline WO3 with an average grain size of less than 100nm, the average grain size of NiO is 0.7μm, and the average grain size of Fe2O3 is 0.6μm; the rotation speed of the dry mixing crushing and dispersion is 250rpm, and the time is 4h;
[0045] Step 2: uniformly mix the pretreated tungsten source, nickel source and iron source powders obtained in step 1 with the nano carbon black particles with the aid of anhydrous ethanol solution, and obtain a mixture after drying; the average particle size of the nano carbon black particles is 30nm, and the nano carbon black particles are amorphous structures, the mass content of carbon in the nano carbon black particles is 99%, the mass of the nano carbon black particles is 9.2% of the mass of the tungsten source powder, i.e., WO3, and the mass of the anhydrous ethanol solution is 70% of the mass of WO3; the uniform mixing method is wet mixing ball milling, the speed used is 250rpm, and the time is 3h;
[0046] Step 3: The mixture obtained in step 2 is laid to a material layer thickness of 25 mm and then subjected to a two-stage carbon thermal reduction treatment. The mass purity of the argon atmosphere used is greater than 99.99%. The reduction temperatures of the two-stage carbon thermal reduction treatment are 650° C. and 1050° C., and the time is 3 h, to obtain a pre-reduced powder with an average particle size of 150 nm;
[0047] Step 4: After the pre-reduced powder obtained in step 3 is spread to a material layer thickness of 20 mm, a deep hydrogen reduction treatment is performed, and the mass purity of the hydrogen atmosphere used is greater than 99.99%, to obtain an ultrafine tungsten-nickel-iron composite powder; the deep hydrogen reduction treatment is: heating to 850°C at a heating rate of 5°C / min and then keeping warm for 3 hours.
[0048] According to the test, the average particle size of the ultrafine tungsten-nickel-iron composite powder prepared in this embodiment is 220 nm.
[0049] Example 3
[0050] This embodiment includes the following steps:
[0051] Step 1: dry-mix WO3, NiO and Fe2O3 powders to obtain pre-treated tungsten source, nickel source and iron source powders; the mass of the WO3, NiO and Fe2O3 powders is measured according to 93% W-4.9% Ni-2.1% Fe; the average particle size of the WO3 is 48 μm, and the specific surface area is greater than 7 g / cm 3 , composed of nanocrystalline WO3 with an average grain size of less than 100nm, the average grain size of NiO is 0.8μm, and the average grain size of Fe2O3 is 0.9μm; the rotation speed of the dry mixing crushing and dispersion is 300rpm, and the time is 4h;
[0052] Step 2: uniformly mix the pretreated tungsten source, nickel source and iron source powders obtained in step 1 with the nano carbon black particles with the aid of anhydrous ethanol solution, and obtain a mixture after drying; the average particle size of the nano carbon black particles is 30nm, and the nano carbon black particles are amorphous structures, the mass content of carbon in the nano carbon black particles is 99%, the mass of the nano carbon black particles is 10.1% of the mass of the tungsten source powder, i.e., WO3, and the mass of the anhydrous ethanol solution is 60% of the mass of WO3; the uniform mixing method is wet mixing ball milling, the speed used is 250rpm, and the time is 4h;
[0053] Step 3: The mixture obtained in step 2 is laid to a material layer thickness of 22 mm and then subjected to a two-stage carbon thermal reduction treatment. The mass purity of the argon atmosphere used is greater than 99.99%. The reduction temperatures of the two-stage carbon thermal reduction treatment are 650° C. and 1100° C., and the time is 3 h, to obtain a pre-reduced powder with an average particle size of 200 nm;
[0054] Step 4: After the pre-reduced powder obtained in step 3 is spread to a material layer thickness of 25 mm, a deep hydrogen reduction treatment is performed, and the mass purity of the hydrogen atmosphere used is greater than 99.99%, to obtain an ultrafine tungsten-nickel-iron composite powder; the deep hydrogen reduction treatment is: heating to 850°C at a heating rate of 5°C / min and then keeping warm for 3 hours.
[0055] According to the test, the average particle size of the ultrafine tungsten-nickel-iron composite powder prepared in this embodiment is 250 nm.
[0056] Example 4
[0057] This embodiment includes the following steps:
[0058] Step 1: dry-mix WO3, NiO and Fe2O3 powders to obtain pre-treated tungsten source, nickel source and iron source powders; the mass of the WO3, NiO and Fe2O3 powders is measured according to 93% W-4.9% Ni-2.1% Fe; the average particle size of the WO3 is 50 μm, and the specific surface area is greater than 7 g / cm 3 , composed of nanocrystalline WO3 with an average grain size of less than 100nm, the average grain size of NiO is 1μm, and the average grain size of Fe2O3 is 1μm; the rotation speed of the dry mixing crushing and dispersion is 250rpm, and the time is 6h;
[0059] Step 2: uniformly mix the pretreated tungsten source, nickel source and iron source powders obtained in step 1 with the nano carbon black particles with the aid of anhydrous ethanol solution, and obtain a mixture after drying; the average particle size of the nano carbon black particles is 30nm, and the nano carbon black particles are amorphous structures, the mass content of carbon in the nano carbon black particles is 99%, the mass of the nano carbon black particles is 10.5% of the mass of the tungsten source powder, i.e., WO3, and the mass of the anhydrous ethanol solution is 60% of the mass of WO3; the uniform mixing method is wet mixing ball milling, the speed used is 250rpm, and the time is 4h;
[0060] Step 3: The mixture obtained in step 2 is laid to a material layer thickness of 20 mm and then subjected to a two-stage carbon thermal reduction treatment. The mass purity of the argon atmosphere used is greater than 99.99%. The reduction temperatures of the two-stage carbon thermal reduction treatment are 650° C. and 1100° C., and the time is 4 hours to obtain a pre-reduced powder with an average particle size of 300 nm.
[0061] Step 4: The pre-reduced powder obtained in step 3 is spread to a layer thickness of 25 mm and then subjected to deep hydrogen reduction treatment. The mass purity of the hydrogen atmosphere used is greater than 99.99% to obtain an ultrafine tungsten-nickel-iron composite powder; the deep hydrogen reduction treatment is as follows: heating to 900°C at a heating rate of 5°C / min and then keeping warm for 4 hours.
[0062] According to the test, the average particle size of the ultrafine tungsten-nickel-iron composite powder prepared in this embodiment is 300 nm.
[0063] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing ultrafine tungsten-nickel-iron composite powder, characterized in that: The method comprises the following steps: Step 1: dry-mix, crush and disperse WO3, NiO and Fe2O3 powders to obtain pre-treated tungsten source, nickel source and iron source powders; Step 2: uniformly mixing the pretreated tungsten source, nickel source and iron source powders obtained in step 1 with the nano carbon black particles with the aid of an anhydrous ethanol solution, and obtaining a mixture after drying; Step 3: After the mixture obtained in step 2 is laid, it is subjected to a segmented carbon thermal reduction treatment to obtain a pre-reduced powder; Step 4: Lay the pre-reduced powder obtained in step 3 and perform deep hydrogen reduction treatment to obtain ultrafine tungsten-nickel-iron composite powder.
2. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The mass of the WO3, NiO and Fe2O3 powders described in step 1 is measured according to 93% W-4.9% Ni-2.1% Fe.
3. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The average particle size of WO3 in step 1 is 40 μm to 50 μm, and the specific surface area is greater than 7 g / cm 3 , composed of nanocrystalline WO3 with an average grain size of less than 100nm, the average grain size of NiO is 0.5μm~1μm, the average grain size of Fe2O3 is 0.5μm~1μm, the rotation speed of the dry mixing crushing and dispersion is 200rpm~300rpm, and the time is 2h~6h.
4. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The average particle size of the nano carbon black particles in step 2 is 20nm to 50nm, and the nano carbon black particles are amorphous structures. The mass content of carbon in the nano carbon black particles is greater than 99%, and the mass of the nano carbon black particles is 7.2% to 10.5% of the mass of the tungsten source powder; the uniform mixing method is wet mixing ball milling, the rotation speed used is 200rpm to 250rpm, and the time is 2h to 4h.
5. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The thickness of the material layer after the mixture is laid in step three is less than 30 mm, the reduction temperature of the segmented carbon thermal reduction treatment is 650°C and 1050°C~1100°C, the reduction time is 2h~4h, and the mass purity of the argon atmosphere used in the segmented carbon thermal reduction treatment is greater than 99.99%.
6. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The average particle size of the pre-reduced powder in step 3 is 100nm to 300nm.
7. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The thickness of the material layer after the pre-reduction powder is laid in step 4 is less than 30 mm, the reduction temperature of the deep hydrogen reduction treatment is 800°C to 900°C, the time is 2h to 4h, and the mass purity of the hydrogen atmosphere used in the deep hydrogen reduction treatment is greater than 99.99%.
8. The method for preparing an ultrafine tungsten-nickel-iron composite powder according to claim 1, characterized in that: The average particle size of the ultrafine tungsten-nickel-iron composite powder described in step 4 is less than 300 nm.
9. An ultrafine tungsten-nickel-iron composite powder, characterized in that: Prepared by the method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing bulk alloy at low temperature through gradient reduction of oxides
CN113414386A
Technology and equipment for preparation of tungsten carbide-nickel-iron series nanometer grade composit powder
CN1220926A
Preparation process of superfine carbide powder by direct reduction carbonization in pipe furnace
CN1321558A
Method for production of composite powders and composite powder
WO2008031122A1
Method for preparing ultrafine tungsten carbide powder by means of one-step carbonization of tungsten oxide
WO2023065457A1